ANALISIS PERFORMA JARINGAN KOMUNIKASI DATA PADA MONITORING DETAK JANTUNG (BPM) MENGGUNAKAN APLIKASI SMARTPHONE BERBASIS WEMOS - Jessica Fajrian (2022)
Heart rate monitoring with application on a smartphone is one of the developments in the field of health technology. This monitoring is conducted in real-time from a detection tool to end user through an internet network. Real-time monitoring can allow delays in data transmission that caused by the network, so the received data can't be optimal. Quality of Service (QoS) tests on the network to transmit data BPM from the microcontroller to the database can show the optimal result. More optimal system QoS results obtained by using the Telkomsel network such as 268.076 ms with the "Sangat Baik" category for delay, 0.4108 with the "Sangat Bagus" category for jitter, 7.464 Kbit/s with the "Buruk" category for throughput, and 0% with the "Sangat Bagus" category for packet loss. This QoS test uses equipment that has been made and tested by 10 objects until the application MHA reads the BPM.